2018
DOI: 10.11607/prd.3931
|View full text |Cite
|
Sign up to set email alerts
|

Flapless Postextraction Socket Implant Placement: The Effects of a Platform Switch–Designed Implant on Peri-implant Soft Tissue Thickness—A Prospective Study

Abstract: This paper presents the results of a prospective study on the clinical effect of grafting the buccal gap with platform switching, following flapless tooth extraction and immediate implant placement and provisional restoration, on (1) alterations in buccolingual ridge dimension and (2) midfacial peri-implant soft tissue thickness. Fifty-six patients were placed in one of four treatment groups: (1) a non-platform-switching implant (Non-PS, n = 14); (2) a non-platform-switching implant and bone graft (BG/Non-PS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
0
8
0
3
Order By: Relevance
“…Dental implants incorporating platform-switching (PS) preserve the crestal bone around the top of the implant [13][14][15][16][17] and alter the starting point from which crestal bone remodeling occurs [11]. Following the crestal bone position over time has also shown that the soft tissue stability is also affected by the presence of platformswitching [18]. When analyzing the peri-implant soft tissue with PS implants, Tarnow found that PS seemed to help in preserving the ridge dimensions and enhancing the periimplant soft tissue stability [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental implants incorporating platform-switching (PS) preserve the crestal bone around the top of the implant [13][14][15][16][17] and alter the starting point from which crestal bone remodeling occurs [11]. Following the crestal bone position over time has also shown that the soft tissue stability is also affected by the presence of platformswitching [18]. When analyzing the peri-implant soft tissue with PS implants, Tarnow found that PS seemed to help in preserving the ridge dimensions and enhancing the periimplant soft tissue stability [18].…”
Section: Introductionmentioning
confidence: 99%
“…Following the crestal bone position over time has also shown that the soft tissue stability is also affected by the presence of platformswitching [18]. When analyzing the peri-implant soft tissue with PS implants, Tarnow found that PS seemed to help in preserving the ridge dimensions and enhancing the periimplant soft tissue stability [18]. Accordingly, the present study attempted to verify the influence of PS on soft tissue, by comparing the soft tissue stability around implants with and without PS, during three years of follow-up after the definitive crown placement.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in animal and human clinical studies that thin vertical tissue thickness is associated with bone loss during establishment of peri‐implant mucosa when the implant is placed at the level of osseous crest . The effect of the nonmatched diameter implant on a thin soft tissue biotype remains to be determined . Even with thicker peri‐implant mucosal tissue, a microgap‐related inflammatory response is evident, leading to greater crestal bone remodeling than with supracrestal implant placement …”
Section: Emergence Of Esthetics In Implant Therapymentioning
confidence: 99%
“…27,28 The effect of the nonmatched diameter implant on a thin soft tissue biotype remains to be determined. [28][29][30] Even with thicker peri-implant mucosal tissue, a microgap-related inflammatory response is evident, leading to greater crestal bone remodeling than with supracrestal implant placement. 31 Looking forward, novel abutment and supracrestal componentrelated features will be used to better manage peri-implant and peri-abutment soft tissue attachments.…”
Section: Emerg En Ce Of E S the Ti C S In Impl Ant Ther Apymentioning
confidence: 99%
“…In fact, no statistically significant differences were found for ∆MBL one, three and five at one, three and five years after loading between implant connections (p < 0.05), and statistically significant differences were found for PD between EH and IC implants (1 year follow-up) −0.53 (95%CI −0.82 to −0.24, p = 0.0004). On the contrary, the role of platform switching in implant abutment is still unclear [24,25].…”
Section: Introductionmentioning
confidence: 99%